Re-descubriendo el Espinal Pampeano - Soibelzon, Esteban; Negrete, Javier; Ciai, Dante; Depino, Emiliano (Revista Aves Argentinas, 2023)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).